1993
DOI: 10.1002/jor.1100110114
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating and antitumor activities of 1α,25‐dihydroxyvitamin D3 in vitro and 1α‐hydroxyvitamin D3 in vivo on human osteosarcoma

Abstract: The differentiating and antitumor activities of 1 alpha,25-dihydroxyvitamin D3 (1 alpha,25(OH)2D3) in vitro and 1 alpha-hydroxyvitamin D3 (1 alpha(OH)D3) in vivo were studied with a human osteosarcoma cell line (OST strain). Anti-tumor activity was estimated with the use of 3-(4,5-dimethylthiazol)-2, 5-diphenyltetrazolium bromide (MTT) assay, colony-forming assay, and athymic mouse assay. The intracellular alkaline phosphatase (ALP) activity of tumor cells and production of bone Gla protein (BGP) in culture me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Osteosarcoma is one of the most malignant tumors of animals and humans, and has a high percentage of pulmonary metastasis in its early stages [18]. Canine and human osteosarcoma closely resemble each other in their histological appearance, biological behavior and pathogenesis, hence canine osteosarcoma becomes an excellent model for studying antitumor responses for human osteosarcoma [2,12].While vitamin D and retinoids have been shown to increase the rate at which transformed cells express complex patterns of gene expression, to control cell cycle that leads to differentiation, loss of proliferative capacity and loss of oncogenecity [9,15,17,19] we investigated in the present study whether vitamin D 3 and its derivatives, and the retinoids have the potential for inducing apoptosis in canine osteosarcoma using the POS osteosarcoma cell line.POS canine osteosarcoma cell line, established and characterized directly from a spontaneous osteosarcoma on a femur of a 1.5 year old male mongrel dog [8] were used for this study. These cells were maintained in RPMI-1640 containing 10% heat-inactivated fetal calf serum (FCS), HEPES (2,383 mg/ml), L-glutamine, and antibiotics penicillin (62.5 mg/ml) and streptomycin (100 mg/ml) at 37°C in a humidified atmosphere containing 95% air and 5% CO 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Osteosarcoma is one of the most malignant tumors of animals and humans, and has a high percentage of pulmonary metastasis in its early stages [18]. Canine and human osteosarcoma closely resemble each other in their histological appearance, biological behavior and pathogenesis, hence canine osteosarcoma becomes an excellent model for studying antitumor responses for human osteosarcoma [2,12].While vitamin D and retinoids have been shown to increase the rate at which transformed cells express complex patterns of gene expression, to control cell cycle that leads to differentiation, loss of proliferative capacity and loss of oncogenecity [9,15,17,19] we investigated in the present study whether vitamin D 3 and its derivatives, and the retinoids have the potential for inducing apoptosis in canine osteosarcoma using the POS osteosarcoma cell line.POS canine osteosarcoma cell line, established and characterized directly from a spontaneous osteosarcoma on a femur of a 1.5 year old male mongrel dog [8] were used for this study. These cells were maintained in RPMI-1640 containing 10% heat-inactivated fetal calf serum (FCS), HEPES (2,383 mg/ml), L-glutamine, and antibiotics penicillin (62.5 mg/ml) and streptomycin (100 mg/ml) at 37°C in a humidified atmosphere containing 95% air and 5% CO 2 .…”
mentioning
confidence: 99%
“…While vitamin D and retinoids have been shown to increase the rate at which transformed cells express complex patterns of gene expression, to control cell cycle that leads to differentiation, loss of proliferative capacity and loss of oncogenecity [9,15,17,19] we investigated in the present study whether vitamin D 3 and its derivatives, and the retinoids have the potential for inducing apoptosis in canine osteosarcoma using the POS osteosarcoma cell line.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…POS53B, 53C, and 53D showed high ALP activity compared with POS14A. 1,25(OH)2D3 was added to the culture medium under the same conditions as described by Tsuchiya et al in which an increase in ALP activity was demonstrated in near-confluent culture [32]. The different responses in ALP activity among cell lines to 1,25(OH)2D3 may therefore be due to their maturity: immature cells with low ALP activity were stimulated and mature cells with high ALP activity were suppressed [18].…”
Section: Discussionmentioning
confidence: 97%
“…Sci. 61(6): 649-656, 1999 1,25(OH)2D3 also enhanced antitumor chemotherapy both in vitro and in vivo [32]. TGF-β1, one of the most abundant growth regulatory factors in bone matrix, has complex effects.…”
mentioning
confidence: 99%